A Needs Analysis in Learning English for Airline Staff Program - Rahmat Hidayat (English Education Journal, 2018)
Needs analysis is necessary for the institutions to design or develop the English curriculum to find out a set of competencies needed by the students. Needs analysis to find specific needs for the students in the institution may direct the institution to an English program called English for Specific Purposes (ESP). This study was aimed (1) to find out the students of Airline Staff Program need in learning English at International Tourism College and (2) to investigate in what extent the existing English syllabus appropriate to the students’ needs. A purposive sampling technique was used to choose the sample. The subjects were 71 students of Airline Staff Program, the lecturer and the manager of International Tourism College. The instruments were close ended-questionnaire, documentation, and interview guide. The collected data were analyzed and interpreted through qualitative and quantitative procedures, by using data reduction, presentation, verification and conclusion drawing.  The first finding showed that students need to learn English because English is an international language that is used at airline industry. The students need to learn four skills; speaking, listening, reading and writing. However, communication and speaking skill are the main priorities skill for them. The second was from documentation. It is found that the syllabus is appropriate with the students’ need related to duration of the course, material, and context. The study also showed some aspects of teaching material should be upgraded in developing a communicative syllabus. Finally, by analyzing students’ need helped teachers and institution in designing an appropriate syllabus.